2013
DOI: 10.1105/tpc.113.114009
|View full text |Cite
|
Sign up to set email alerts
|

WRKY6 Transcription Factor Restricts Arsenate Uptake and Transposon Activation in Arabidopsis

Abstract: Stress constantly challenges plant adaptation to the environment. Of all stress types, arsenic was a major threat during the early evolution of plants. The most prevalent chemical form of arsenic is arsenate, whose similarity to phosphate renders it easily incorporated into cells via the phosphate transporters. Here, we found that arsenate stress provokes a notable transposon burst in plants, in coordination with arsenate/phosphate transporter repression, which immediately restricts arsenate uptake. This repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
144
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 181 publications
(148 citation statements)
references
References 57 publications
4
144
0
Order By: Relevance
“…1a,b). As(V) tolerance can be associated with slow As(V) uptake 11,16,17 and correlates with enhanced arsenic accumulation 8,11 . We observed that Col accumulated three times more arsenic than Kas-1 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1a,b). As(V) tolerance can be associated with slow As(V) uptake 11,16,17 and correlates with enhanced arsenic accumulation 8,11 . We observed that Col accumulated three times more arsenic than Kas-1 ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In plants, arsenic tolerance is critical for adaptation to specific soils and has determined plant distribution 4,5 ; the molecular mechanisms are analyzed mainly by studying proteins presumably involved in arsenate (As(V)) tolerance based on sequence homology with bacterial and yeast proteins 6,7 . Genetic approaches are little used to study As(V) tolerance mechanisms [8][9][10][11][12] , and the genes implicated in natural intraspecific variation are unknown [13][14][15] .…”
mentioning
confidence: 99%
“…Because TEs can change their position within a genome, they are considered important factors associated with genome reorganization and epigenetic changes [73,74]. Furthermore, transposon activity can be influenced by either environmental stress [75,76] or genomic changes, including polyploidy [77]. In polyploids, changes in transposon activity are twofold, with effects on both transcriptional activity and transpositional activity.…”
Section: (E) Transposons and Noveltymentioning
confidence: 99%
“…In response to As(V), expression of the As(V)/Pitransporter gene PHT1;1 is quickly repressed, which provides an efficient strategy for As(V) tolerance (Castrillo et al, 2013). CK acts as a negative regulator of PHT1;1 expression in response to Pi starvation (Martín et al, 2000;Franco-Zorrilla et al, 2002;Wang et al, 2006).…”
Section: Ck-deficient Plants Have An Enhanced As(v) Tolerance Phenotypementioning
confidence: 99%
“…To further understand the basis of CK depletion in response to As(V), we compared a transcriptome profile of the As(V) response (Castrillo et al, 2013) with a meta-analysis of CK microarray data (Brenner and Schmülling, 2015). We found that As(V) down-regulates a significant number of genes that are considered CK core-inducible (36 of 65 TOP65CytK), including CK biosynthesis genes and response regulator genes (Table 1; Supplemental Table S1).…”
Section: As(v) Reduces Endogenous Ck Levelsmentioning
confidence: 99%